Rethinking the MBA through Hip Hop innovation and Hip Hop innovators: Fat Joe and DJ Khaled pair with two sport × entertainment faculty - Harrison, C. Keith; Saunders, Reggie; Griffin, Whitney; Bukstein, Scott; Porter, Jeffrey; Martin, Brandon (Frontiers in Sports and Active Living, 2024)
Theory without relevance for practice in a professional graduate degree has been critiqued by some scholars as a deficit approach when preparing MBA students for the workforce. Scholars and practitioners alike call for more pedagogy in the curriculum with a focus on innovation, creativity, and the involvement of industry practitioners. This paper serves as a case study of a moment in time on Monday, 14 June 2021, when the concept of “pracademics” was realized between two artists and two faculty. Following the transcription of the dialogue between two guest speakers from the Hip Hop world (i.e., Fat Joe and DJ Khaled) and two faculty from the sport management MBA program, the paper analyzes the deeper meaning of their intellectual presence with their expertise in the business of culture (i.e., Hip Hop). Findings reveal how the pairing of Hip Hop artists and faculty in an MBA program can address the innovation gap within global business curricula and models. The broader umbrella of pedagogy and application has implications for other academic disciplines to embrace this concept of pairing academics and industry practitioners.